2011
DOI: 10.3892/ijo.2011.951
|View full text |Cite
|
Sign up to set email alerts
|

(-)-Epigallocatechin-3-gallate induces apoptosis in gastric cancer cell lines by down-regulating survivin expression

Abstract: Abstract. The polyphenol (-)-epigallocatechin-3-gallate (EGCG) is a green tea constituent, which has been shown to inhibit cancer cell growth in vitro, in vivo and in epidemiological studies. In this study, we investigated its effects in gastric cancer cell lines. Five gastric cancer cell lines, the MKN-1, MKN-28, MKN-45, NUGC-3 and TMK-1, were found to be sensitive to EGCG treatment. Of all the cell lines tested, NUGC-3 was the most sensitive. EGCG treatment of NUGC-3 cells induced apoptosis, which was confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…While at higher concentration (>20 μM), it exhibited anti-proliferation activities through induction of G 2 /M cell cycle arrest but not apoptosis [44]. Another study found that several gastric cancer cell lines were sensitive to EGCG (100 μM) induced apoptosis due to inhibition of survivin, a potent anti-apoptotic protein [45]. Many signaling pathways might be affected by EGCG treatment.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…While at higher concentration (>20 μM), it exhibited anti-proliferation activities through induction of G 2 /M cell cycle arrest but not apoptosis [44]. Another study found that several gastric cancer cell lines were sensitive to EGCG (100 μM) induced apoptosis due to inhibition of survivin, a potent anti-apoptotic protein [45]. Many signaling pathways might be affected by EGCG treatment.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…There are conflicting reports of apoptotic and nonapoptotic cell death induced by compound 4 , and the exact molecular mechanisms have not been fully elucidated yet. However, most of the previous reports have concluded that this compound induces caspase-mediated apoptosis in various tumor cells via the mitochondrial pathway [44,45] or via the death receptor [46,47,48]. Conversely, several reports demonstrated the involvement of nonapoptotic cell death, such as caspase-independent necrosis-like cell death [49] or reactive oxygen species (ROS)-mediated lysosomal membrane permeabilization [50].…”
Section: Discussionmentioning
confidence: 99%
“…EGCG is recognized as a chemopreventive agent, which is inversely correlated with the prevalence of various cancer types, including breast, prostatic, colonic, mammary, ovarian and pancreatic cancers [37-39]. In most of these cancers, survivin has been shown to be a molecular target of EGCG, in which increased survivin levels are suppressed by EGCG treatment [40-42]. Nonetheless, in non-cancer diseases, the relationship between EGCG and the expression of survivin splice variants has not been reported prior to this study.…”
Section: Discussionmentioning
confidence: 99%